Comparative Study on Histological Structure of Gill of Rasbora cephalotaeniaBleeker, 1852 from the waters around Stadion Utama Riau and Kandis River Riau Province - Lailatul Saktiawan; Eddiwan Eddiwan; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Rasbora cephalotaenia is present in the waters around Stadion Utama Riau that has relatively good water quality, as well as in the Kandis River that has polluted waters. The water condition of the rivers may affect the fish health status in general. A study aims to understand the histological structure of the gill of fish from the Kandis River and the waters around Stadion Utama Riau has been conductedfrom March-April 2018.Gill structure’s abnormality was identified using Histopathological Alteration Index (HAI). Histological structure of the gill of fish from both areas are different. The cell structure of the Kandis’s fish has more abnormalities compared to that of the fish from Stadion Utama Riau. Results shown that the types of abnormality present were hyperplasia, hypertrophy, athrophy, deformated lamella, congestion, odema and epithelium rupture.The HAIof theR. cephalotaenia from the waters around Stadion Utama Riau was 3.8, indicated that the gill was normal, while the HAIof the R. cephalotaeniafrom the Kandis River was 12,indicated that the gill was slightly damaged. Keywords: Histopathological Alteration Index, hyperplasia, hypertrophy, atrophy, ruptured epitelium.